Recent thermokarst evolution in the Italian Central Alps. (27th January 2021) - Guglielmin, Mauro; Ponti, Stefano; Forte, Emanuele; Cannone, Nicoletta
Abstract: Thermokarst depressions are widespread phenomena due to permafrost degradation in the Arctic, whereas only few are known from mountain permafrost of the mid‐latitudes. In the Italian Central Alps, close to the Stelvio Pass (2, 763 m above sea level), a ski run was built in 1987. Since 1981, statistically significant air warming has been recorded, especially during summer (+0.65°C per decade). Permafrost temperature recorded at the nearby Share Stelvio Borehole between 1990 and 2011 exhibited a rapid increase (> 0.8°C per decade) and an active‐layer thickening (7 cm/year). Between the years 1999 and 2003, some thermokarst depressions started to develop, initially in the lower part of the ski run and then extending to higher elevations. The depressions increased in number, size, and depth with time. Since ski‐run construction, the area remained free of vegetation until early 2000, when vegetation colonization started, showing a coupling with the onset of thermokarst development and summer warming. Vegetation changes accelerated with the ingress of pioneer and early‐successional as well as of late‐successional species. Moreover, the ingress of shrub species ( Salix spp.) typical of lower elevation belts (subalpine and even montane) was dated to 2004. All the observed features show a rapid and coupled response of the abiotic and biotic components of this ecosystem to climate warming. Our data also confirm the similarity of the observed responses and dynamics of the alpine tundra with the Arctic tundra with regard to both permafrost and vegetation.